PSYCHOLOGICAL IMPLICATIONS OF ADVANCED CARDIAC SCREENING: NO DIFFERENCES IN ANXIETY LEVELS BASED ON REASON FOR FALSE POSITIVE RESULT. Issue 7 (11th March 2014) - Asif, I; Price, D; Jenkins, J; Lett, A; Irwin, M; Johnson, S; Toresdahl, B; Pelto, H; Smith, T; Harmon, K; Drezner, J
Abstract : Background: The American Heart Association (AHA) cites excessive anxiety in athletes with false positive results as a major deterrent to ECG screening during the PPE. No study has examined the experiences of athletes with false positive test results during cardiovascular screening. Objective: To determine the psychological impact of young athletes with false positive results by history, exam, or ECG during cardiovascular screening. Design: Prospective, multi-site investigation (22 schools). Setting: Young competitive athletes. Participants: 1 506 high school athletes (59.3% male, mean age 15.5 years, 53.7% Caucasian, 23.4% African American). Assessment of risk factors: Athletes underwent screening with a standardized AHA-based history and physical exam and ECG. Main outcome measurements: Pre- and post-screen validated assessments for health attitudes, anxiety, and impact of screening on sport. Results: 74.1% of athletes had normal screens, 22.1% false positive results (12.9% history, 4.2% exam, 3.1% ECG), and 0.9% were diagnosed with a cardiac disorder. Before screening, females preferred to know about underlying cardiac conditions compared to males (P<.001). African-Americans were less concerned (P<.001) and less interested (P<.001) in cardiac screening compared to Caucasians. As a group, athletes did not report anxiety during screening and there were no differences in anxiety levels among athletes screening normal or false positive (P=.69). There were no differences in anxiety levels based on reason for false positive result (history, exam, or ECG) both during (P=.95) and after (P=.40) screening. Athletes with false positive outcomes reported they would recommend ECG screening and that it positively impacted their training. Athletes diagnosed with disease described anxiety after screening completion, but felt all athletes should receive an ECG prior to competition. Conclusions: The AHA supposition that ECG screening causes excessive anxiety in athletes with false positive results is unsubstantiated. Psychological distress should not be used as a rationale against ECG screening.